In vitro antibacterial activity of essential oils from Eryngium foetidum L. and Clinopodium brownei (Sw.) Kuntze - Ortiz-Ruíz, Marianella; Navarro-Mengual, Jesús David; Jaramillo-Colorado, Beatriz E. (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2024)
In the present work, the volatile chemical composition of the essential oils was determinated from Colombian Eryngium foetidum L. and Clinopodium brownei (Sw.) Kuntze, extracted by hydrodistillation, using gas chromatography coupled with mass spectrometry (GC-MS) technique. The essential oil of E. foetidum leaves is composed mostly of aliphatic aldehydes, mainly 2-dodecenal (43.0%), while in the essential oil of the aerial parts of C. brownei were menthone (54.3%), pulegone (17.7%), and neomenthol (16.1%). The susceptibility of the bacterial strains Staphylococcus aureus subsp. aureus (ATCC 11632), Escherichia coli (ATCC 25922), Klebsiella pneumoniae (ATCC 13883), and Pseudomonas aeruginosa (ATCC 27853) to both essential oils was tested with agar diffusion assays. It was found that E. foetidum essential oil inhibits the growth of S. aureus (90% at 150 µg mL-1). Broth microdilution tests determined that the MIC and MBC of the E. foetidum essential oil against S. aureus were 105 and 150 μg mL-1, respectively. 2-dodecenal had strong antibacterial activity against S. aureus with MIC and MBC of 105 μg mL-1 (98%). Binary combinations of 2-dodecenal and S-limonene or 2,4,6-trimethoxybenzaldehyde had an indifferent effect in checkerboard tests, so it could be stated that the antibacterial activity of the essential oil of Eryngium foetidum is mainly due to the action of the 2-dodecenal.